2019
DOI: 10.1038/s41467-019-09535-w
|View full text |Cite
|
Sign up to set email alerts
|

Plant leaves inspired sunlight-driven purifier for high-efficiency clean water production

Abstract: Natural vascular plants leaves rely on differences in osmotic pressure, transpiration and guttation to produce tons of clean water, powered by sunlight. Inspired by this, we report a sunlight-driven purifier for high-efficiency water purification and production. This sunlight-driven purifier is characterized by a negative temperature response poly(N-isopropylacrylamide) hydrogel (PN) anchored onto a superhydrophilic melamine foam skeleton, and a layer of PNIPAm modified graphene (PG) filter membrane coated out… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
131
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 185 publications
(134 citation statements)
references
References 53 publications
0
131
0
Order By: Relevance
“…Geng et al recently demonstrated an interesting plant leaf inspired solar water purifier (Figure 10c), by means of transpiration/guttation effect triggered by sunlight, liquid clean water is repelled from the tailored PNPG‐F structure, offering an extremely high water collection of 4.2 kg m −2 h −1 under 1 sun. [ 127 ]…”
Section: Enhanced Solar Evaporationmentioning
confidence: 99%
“…Geng et al recently demonstrated an interesting plant leaf inspired solar water purifier (Figure 10c), by means of transpiration/guttation effect triggered by sunlight, liquid clean water is repelled from the tailored PNPG‐F structure, offering an extremely high water collection of 4.2 kg m −2 h −1 under 1 sun. [ 127 ]…”
Section: Enhanced Solar Evaporationmentioning
confidence: 99%
“…(iv) Polyurethane foam: The carrier molecules are made of foam with high mesoporous structure. It is efficient to treat wastewater because of the coating of hydrogels and aerogels [24]. (v) Biofilms: This type of carrier molecules utilizes photocatalytic materials along with their adherent microorganism to treat the wastewater.…”
Section: Carrier Moleculesmentioning
confidence: 99%
“…Among various desalination technologies, such as reverse osmosis and ion exchange, the solar still is distinguishable due to its low energy consumption and little impairment on natural freshwater ecosystems 2, 3 . To promote practical application of the solar still, it has been long developed from bottom heating model, bulk heating model to interfacial heating model with increasing solar efficiency and reducing cost 3–8 . In the interfacial heating model, solar energy is localized at the evaporation surface by high light absorption and low thermal conduction to bulk water using a floating structure 9 .…”
Section: Introductionmentioning
confidence: 99%
“…2,3 To promote practical application of the solar still, it has been long developed from bottom heating model, bulk heating model to interfacial heating model with increasing solar efficiency and reducing cost. [3][4][5][6][7][8] In the interfacial heating model, solar energy is localized at the evaporation surface by high light absorption and low thermal conduction to bulk water using a floating structure. 9 Attention has mainly focused on high absorption in the solar spectrum, low thermal loss from the evaporation surface and sufficient water supply for evaporation.…”
Section: Introductionmentioning
confidence: 99%